Computer-Aided Drug Design : QSAR, Molecular Docking, Virtual Screening, Homology and Pharmacophore Modeling - Thakur, Aman; Goutam, Kiran; Mehta, Vineet; Nagu, Priyanka (De Gruyter Textbook, 2024)
Computer-Aided Drug Design (CADD) is a comprehensive guide designed for both beginners and experienced users in CADD. This book covers the fundamental principles and gradually delves into more advanced concepts and techniques, making it an invaluable resource to anyone interested in CADD. It begins by establishing a solid foundation, explaining the core concepts of CADD, the user interface and essential tools. It covers QSAR, molecular docking, homology modeling, virtual screening, pharmacophore modeling, ensuring that the reader can quickly become proficient in CADD. The book provides in-depth insights into 3D modeling, rendering, and parametric design. The style of the book is simple, every topic begins from the very basics and explores advanced levels with clarity. Practical examples, step-by-step tutorials and hands-on exercises, are included for better understanding.